Understanding the role of household hygiene practices and foodborne disease risks in child stunting: a UKRI GCRF Action Against Stunting Hub protocol paper - Dominguez-Salas, Paula; Waddington, H.S.; Grace, Delia; Bosire, Caroline; Moodley, Arshnee; Kulkarni, B.; Dasi, T.; Banjara, S.K.; Kumar, R.N.; Fahmida, U.; Htet, M.K.; Sudibya, A.R.P.; et al. (BMJ, 2024)
Introduction Environmental hygiene and food safety are important determinants of child stunting. This research aims to explore the relationship between child stunting and household hygiene practices and behaviours, including the availability of water, sanitation and hygiene (WASH) facilities; the use of safe food and good quality drinking water (especially when used for complementary feeding); hygienic practices in food transport, storage and preparation and the control of cross-contamination from animals, their produce and waste.